Inisiasi Tunas Acacia Hibrid (Acacia mangium x A.Auriculiformis) Secara In Vitro - Sri Sunarti; Asri Insiana Putri (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2009)
Preliminary shoot groeth on acacia hybrids (Acacia mangium x A. Auriculiformis) was observed to assess their in- vitro shoot initiation. Explants were taken from 4 months old seedlings of A. Mangium, A. Auriculiformis and their hybrid. Murashige & Skoog’s (MS) medium was used supplemented with various concentration of BAP, IBA,NAA, and GA4. Parameters measured were bud breaking, number average number of leaves of acacia hybrid was 7 and 1.9 cm and 5.2 respectively, found in medium Ak2 culture. Bud breaking of acacia hybrids on that medium happened 15 days earlier than pure Acacia. This finding showed that acacia hybrid could be propagated by micro propagation succesfully.